Rationale and design for the study of recombinant human hepatocyte growth factor plasmid in the treatment of patients with chronic limb-threatening ischemia (HOPE CLTI): Randomized, placebo-controlled, double-blind, phase III clinical trials - Di, Xiao; Liu, Changwei; Ni, Leng; Ye, Wei; Rong, Zhihua; Zhang, Rui; Niu, Shuai; Li, Fengshi; Zheng, Yuehong; Han, Chengquan; Liu, Yue (The American heart journal, 2022)
Although patients with CLTI have benefited from the rapid development of endovascular techniques, many patients are considered unsuitable for revascularization procedures. A previous phase II clinical trial has suggested that recombinant human hepatocyte growth factor plasmid (NL003) can salvage limbs during the treatment of patients with CLTI. However, the safety and efficacy of this drug need to be evaluated in a larger cohort. HOPE CLTI is a multicenter, randomized, double-blind, placebo-controlled phase III clinical study to evaluate the efficacy and safety of intramuscular injection of NL003 in CLTI patients. This study consisted of 22 trials: HOPE CLTI-1, which includes patients with rest pain (Rutherford stage 4), and HOPE CLTI-2, which includes patients with limb ulcers (Rutherford stage 5). In both trials, patients are randomized with a 2:1 ratio of intramuscular injection of NL003 to placebo. The primary endpoint of HOPE CLTI-1 is the complete pain relief rate. The primary endpoint of HOPE CLTI-2 is the complete ulcer healing rate. The safety endpoint was assessed based on adverse events after injection of NL003. Enrollment began in July 2019. The HOPE CLTI-1 trial aims to complete the randomization of at least 300 patients, while the HOPE CLTI-2 trial aims to enroll at least 240 patients. Both trials are organized such that patients will be followed for 6 months after the first intramuscular injection. HITOP CLTI, which is comprised of 2 multicenter, double-blind, placebo-controlled phase III clinical trials, aims to evaluate the efficacy and safety of the intramuscular administration of NL003 in patients with CLTI.